Efficacy of Internal Heat Acupuncture Combined with High-Voltage Long-Duration Pulsed Radiofrequency on Subacute Postherpetic Neuralgia: A Retrospective Study - Yong Fei; Ming Yao; Bing Huang; Longsheng Xu; Beibei Liu (Pain Research and Management)
Objectives. This study aims at investigating the internal heat acupuncture (IHA) combined with the high-voltage long-duration pulsed radiofrequency (PRF) therapeutic effect on subacute postherpetic neuralgia (PHN). Methods. This retrospective study comprised 81 cases with PHN. They were divided into three groups: IHA combined with the high-voltage long-duration PRF group (IHA-PRF), intradermal injection combined with the high-voltage long-duration PRF group (II-PRF), and the high-voltage long-duration PRF group. The pain numerical rating score (NRS), IL-6, Gal-3, and blood glucose levels were recorded before and after treatment. Results. Compared with before treatment, NRS scores of the three groups were all decreased at each time point. NRS scores of the IHA-PRF group patients decreased significantly in comparison to the PRF group at 1, 4, 8, and 12 weeks following treatment, while group II-PRF only decreased significantly at one week following treatment. Compared with groups II-PRF and PRF, respectively, IL-6 and Gal-3 levels in plasma of patients in group IHA-PRF were significantly decreased at 4 and 12 weeks after treatment. The effective rate of group IHA-PRF was 88.9%, which was considerably more than the other groups, II-PRF (63.0%) and PRF (63.0%). Compared with group II-PRF, patients’ blood glucose levels in IHA-PRF and PRF groups significantly decreased three days and one week after treatment. Conclusion. Internal heat acupuncture combined with high-voltage long-duration pulsed radiofrequency has a satisfactory therapeutic effect on subacute PHN and has no obvious adverse reactions, which is especially suitable for patients with poor blood glucose control.